Management of Educators and Education Personnel from an Islamic Perspective - Wahyudi, Dadeng; Sa’diyah, Maemunah; Indra, Hasbi; Handrianto, Budi (PPSDP International Journal of Education, 2024)
This article discusses the concept of management of teaching staff and educational staff from an Islamic perspective. The type of research used in searching for data is a library research study. This article explores Islamic principles that can be applied in managing human resources in educational institutions. The results of the study show that Islamic values ​​such as trust, fairness, shura, and ihsan have strong relevance to modern management practices, and can provide a solid ethical foundation for the management of teaching and education personnel. Several important things discussed in the implementation of Islamic teaching and education management in educational institutions include: (1) planning, (2) recruitment and selection, (3) development and training, (4) performance assessment, (5) compensation and rewards. Thus, teaching and educational staff in an Islamic perspective not only aim to achieve organizational effectiveness, but also to form individuals who are professionally and spiritually qualified.